A Comparison of Reliability and Construct Validity between the Original and Revised Versions of the Rosenberg Self-Esteem Scale - Tinakon W. (2014)
Objective: The Rosenberg Self-Esteem Scale (RSES) is a widely used instrument that has been tested for reliability and validity in many settings; however, some negative-worded items appear to have caused it to reveal low reliability in a number of studies. In this study, we revised one negative item that had previously (from the previous studies) produced the worst outcome in terms of the structure of the scale, then re-analyzed the new version for its reliability and construct validity, comparing it to the original version with respect to fit indices. Methods: In total, 851 students from Chiang Mai University (mean age: 19.51±1.7, 57% of whom were female), participated in this study. Of these, 664 students completed the Thai version of the original RSES - containing five positively worded and five negatively worded items, while 187 students used the revised version containing six positively worded and four negatively worded items. Confirmatory factor analysis was applied, using a uni-dimensional model with method effects and a correlated uniqueness approach. Results: The revised version showed the same level of reliability (good) as the original, but yielded a better model fit. The revised RSES demonstrated excellent fit statistics, with χ 2=29.19 (df=19, n=187, p=0.063), GFI=0.970, TFI=0.969, NFI=0.964, CFI=0.987, SRMR=0.040 and RMSEA=0.054. Conclusion: The revised version of the Thai RSES demonstrated an equivalent level of reliability but a better construct validity when compared to the original. © 2012 Korean Neuropsychiatric Association.